MENINGKATKAN PERCAYA DIRI BERBICARA BAHASA INGGRIS DI CAHAYA ANAK NEGERI BEKASI - Enny Diah Astuti; Retno Setya Budiasningrum; Rahmi Rosita; Dyan Yuliana; Jajang Setiawan; Ali Satri Efendi (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2022)
Self-confidence is a very important aspect for a person to develop his potential. The higher the confidence to speak in English, the smoother it will be to get the expected results. If you liken it, self-confidence is a key to open the door of doubt that has been a hindrance when you are trying to find a way out. The training method carried out is adjusted to the goal to be achieved, namely to increase self-confidence in speaking English. According to the needs of children, the material that needs to be developed at the Bekasi State Children's Light Community Service place was chosen, the theme "Self-Introduction and PostCard Writing in English" was chosen. Speech practice is usually one of the stages that is considered the most strenuous. It needs to be trained continuously to increase self-confidence in children when speaking English.